Differential Urinary Microbiota Composition Between Women With and Without Recurrent Urinary Tract Infection - Huang, Lei; Li, Xiangyan; Zheng, Bo; Li, Pengtao; Wei, Dali; Huang, Chenwei; Sun, Liying; Li, Haixia (Frontiers in Microbiology, 2022)
Background: Recurrent urinary tract infection (RUTI) is common and burdensome in women. Due to the low concentration or slow-growing of uropathogens in RUTI, standard urine cultures are often negative. Next generation sequencing (NGS) of bacterial 16S rRNA gene is more sensitive, and could be used to reveal the differential microbiota between RUTI patients and asymptomatic controls. Methods: women (aged ≥18 years) of clinically diagnosed RUTI with negative standard urine culture and age-matched women asymptomatic controls with normal urinalysis were enrolled. Their midstream voided urine specimens were collected and processed for NGS (Illumina MiSeq) targeting bacterial 16S rRNA gene V3-V4 region. The dataset was clustered into operational taxonomic units (OTUs) using QIIME. Taxonomic analysis, alpha diversity, beta diversity, multivariate statistical analysis, and LEfSe for differential analysis were performed and compared between RUTI patients and asymptomatic controls. Results: A total of 90 RUTI patients and 62 asymptomatic controls were enrolled in this study. Among them, 74.4% (67/90) and 71.0% (44/62) were successfully amplified and sequenced their bacterial 16S rRNA gene. In alpha diversity analysis, the chao1 index and observed species index were significantly lower in RUTI group than in control group (P=0.015 and 0.028, respectively). In beta diversity analysis, there was significant difference between the 2 groups (ANOSIM, R=0.209, P=0.001). The relative abundance of 36 bacterial taxa was significantly higher and another 24 kinds of bacteria was significantly lower in RUTI group compared with control group (LEfSe analysis, P<0.05, LDA score >3), suggesting Ralstonia, Prevotella, Dialister, Corynbacterium may play an important role in RUTI. Conclusions: The urinary microbiota of women with clinically-diagnosed RUTI was significantly different from age-matched asymptomatic controls.